Extension and validation of a GPU‐Monte Carlo dose engine gDPM for 1.5 T MR‐LINAC online independent dose verification. Issue 10 (28th August 2021) - Li, Yongbao; Ding, Shouliang; Wang, Bin; Liu, Hongdong; Huang, Xiaoyan; Song, Ting
Abstract: Purpose: To extend and validate the accuracy and efficiency of a graphics processing unit (GPU)‐Monte Carlo dose engine for Elekta Unity 1.5 T Magnetic Resonance‐Linear Accelerator (MR‐LINAC) online independent dose verification. Methods: Electron/positron propagation physics in a uniform magnetic field was implemented in a previously developed GPU‐Monte Carlo dose engine–gDPM. The dose calculation accuracy in the magnetic field was first evaluated in heterogeneous phantom with EGSnrc. The dose engine was then commissioned to a Unity machine with a virtual two photon‐source model and compared with the Monaco treatment planning system. Fifteen patient plans from five tumor sites were included for the quantification of online dose verification accuracy and efficiency. Results: The extended gDPM accurately calculated the dose in a 1.5 T external magnetic field and was well matched with EGSnrc. The relative dose difference along central beam axis was less than 0.5% for the homogeneous region in water–lung phantom. The maximum difference was found at the build‐up regions and heterogeneous interfaces, reaching 1.9% and 2.4% for 2 and 6 MeV mono‐energy photon beams, respectively. The root mean square errors for depth–dose fall‐off region were less than 0.2% for all field sizes and presented a good match between gDPM and Monaco GPUMCD. For in‐field profiles, the dose differences were within 1% for cross‐plane and in‐plane directions for all calculated depths except dmax. For penumbra regions, the distance‐to‐agreements between two dose profiles were less than 0.1 cm. For patient plan verification, the maximum relative average dose difference was 1.3%. The gamma passing rates with criteria 3% (2 mm) for dose regions above 20% were between 93% and 98%. gDPM can complete the dose calculation for less than 40 s with 5 × 10 8 photons on a single NVIDIA GTX‐1080Ti GPU and achieve a statistical uncertainty of 0.5%–1.1% for all evaluated cases. Conclusions: A GPU‐Monte Carlo package–gDPM was extended and validated for Elekta Unity online plan verification. Its calculation accuracy and efficiency make it suitable for online independent dose verification for MR‐LINAC.